Organometal Halide Perovskites: Bulk Low‐Dimension Materials and Nanoparticles. (5th February 2015) - González‐Carrero, Soranyel; Galian, Raquel E.; Pérez‐Prieto, Julia
<x xml:space="preserve">Abstract</x> Organometal halide perovskites (hybrid perovskites) contain an anionic metal–halogen‐semiconducting framework and charge‐compensating organic cations. As hybrid materials, they combine useful properties of both organic and inorganic materials, such as plastic mechanical properties and good electronic mobility related to organic and inorganic material, respectively. They are prepared from abundant and low cost starting compounds. The perovskite stoichiometry is associated with the dimensionality of its inorganic framework, which can vary from three to zero, 3D consisting of corner‐sharing MX6 octahedra, and 0D consisting of isolated octahedra. Small‐sized organic cations can fit into the MX6 octahedra of the 3D framework and in all dimensions organic cations surround the inorganic framework. Regarding the low dimensionality in the material, this refers to at least one of its dimensions being shorter than approximately 100 nanometers. These materials should be considered as genuine nanomaterials or as bulk materials depending on whether they have three or less than three dimensions on the nanoscale, respectively. In principle, hybrid perovskite nanoparticles can be prepared with different shapes and with inorganic framework dimensionalities varying from 0D to 3D, and this also applies to the bulk material. This report is mainly focused on the unique properties of organometal halide perovskite nanoparticles.